Determinantes da queda na desigualdade de renda no Brasil - Ricardo Barros; Mirela de Carvalho; Samuel Franco; Rosane Mendonça (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– The extraordinary events that occurred in the country between 2001-2007, with a sharp decline in inequality and the levels of poverty and extreme poverty offers a unique opportunity to examine the most relevant factors to explain changes that benefit the poor and in different scenarios ? with and without economic growth. First, based on a series of counter-factual simulations, we estimate the contribution of these factors to the decline i) in inequality; ii) the percentage of poor; iii) the average gap of poverty; and iv) the severity of poverty. Once that between 2001 and 2003 there was no reduction in poverty, we investigated the contribution of the determining factors for the decline in poverty and extreme poverty only in the subperiod 2003-2007. The results show that the improvements in the distribution of income derived from work per worker and income not derived from the work were the main factors responsible. Demographic changes, which were more favorable to the poor, also stand out when analyzing the reduction in poverty. Secondly, we investigated the extent to which degrees of discrimination and segmentation in the labor market declined in recent years, and quantified their contribution to the recent reduction in the degree of inequality in labor income and per capita income in the country. The results showed that, together, the reduction in various forms of discrimination and segmentation explains 19% of the decrease.
Keywords: D31; I31; I32; 330; Einkommensverteilung; Brasilien